Liability for Religiously Motivated Murder in Muslim Countries - Ammar Abdul Karim, Manna; A. Ignatova, Milena; S. Vasilenko, Alexandra; M. Naurzalieva, Saule; Marjus Jokubo, Murkshtis (International Journal of Psychosocial Rehabilitation, 2020)
There are many cases in today’s world when terrorist acts are committed against persons who have ‘offended the religious feelings’ of Muslims. In this regard, of particular significance is the question of determining in which cases the murder for religious reasons constitutes a criminal act under Islamic law and in which cases it is quite permissible under the current legislation of a particular country. The presented article is devoted to the problems of distinguishing murder for religious reasons from other types of homicide, as well as to establishing the very concept of ‘religious reason’ and defining possible punishment for expressions of religious violence. The study considers the problem of liability for religious violence against the background of the provisions of the main religious sources of Islamic law, the Quran and the Sunnah, and the current criminal legislation of particular countries. Purpose: to form the perception of the role of religious sources in the formation of modern conditional norms on liability for religious violence on the basis of Russian and foreign legal literature, as well as on the analysis of the legislative framework. Methods: The methodological basis of the scientific article consists of a set of methods and techniques of scientific knowledge inherent in the science of law. In particular, the study used comparative legal, dialectical, structural-functional, formal, and logical methods. Results: A distinctive feature of Islamic law is the priority of religious norms, which regulate all spheres of Muslim life. The question of the distinction between religiously motivated murder and crime against life committed for other reasons is addressed in Islamic law not with a view of adequate qualification of the criminal act committed, but with a view of establishing the legitimacy of the murder committed. Conclusions: The murder for religious reasons does not entail criminal punishment in many Muslim countries. The main religious source of Islamic law—the Quran - explicitly prescribes religious violence and killings as a punishment for such acts as apostasy; the Sharia allows for religiously motivated murder for which the perpetrator can avoid criminal liability since the Sharia law considers it as a punishment from Allah. However, it is necessary to distinguish the motive of defection from the motive of religious hatred; the latter is not justified by religious dogma since Islam claims to highly value human life, and no single source of criminal law in the modern Muslim countries contains a call to murder people of another religion. The intentions of religious hatred are often combined with other motives, such as vandalism, etc.; crimes committed on such grounds are subjected to severe punishment. The religious motives that justify committing murder include the riot control and punishments for the rebellion; the latter is due to the perception that the person who raises the revolt is, in fact, rebelling against acceptable and legitimate state power, which is supported by Allah. Apart from apostasy and rebellion, the religious motives justifying the murder also include punishment for ‘blasphemy’ against Allah and Muhammad the Prophet. The legislation of many Muslim states provides for the death penalty for apostasy, whereby a person who has committed a murder for this reason may be either released from punishment or ordered to pay corresponding compensation.